Manajemen Sarana dan Prasarana Pendidikan di TK Islam Terpadu Bunayya 7 - Fauziah Nasution; Masdeani Dasopang; Tiara Winanda; Rahma Yani; Mastianur Daulay (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine the management of educational facilities and infrastructure in the Integrated Islamic Kindergarten Bunayya 7. This research method uses a qualitative approach. The data used from the results of interviews. The results of this study indicate that Bunayya 7 Islamic Integrated Kindergarten is a private school with an “A” accreditation. Not all teachers can apply moral learning in accordance with the demands of the curriculum and the tasks they carry out. Keywords: Teachers, Learning, and Morals